2006
DOI: 10.1007/s10750-006-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of saltwort (Batis maritima L.) in regeneration of degraded mangrove forests

Abstract: While saltwort (Batis maritima L.) is common in the fringe mangrove forests of southwest Florida, its role in regeneration of degraded mangrove communities is not known. Given the potential encroachment and subsequent degradation of mangrove communities by sea-level rise, it is important to quantify the effect of early-colonizing vegetation to early mangrove seedling survival. A greater number of mangrove seedlings were observed in existing B. maritima patches compared to surrounding mudflats. A planting exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 11 publications
3
40
1
1
Order By: Relevance
“…Another important ecological feature of B. maritima is its inability to tolerate prolonged periods of shade in mangrove-dominated wetlands (López-Portillo and Ezcurra, 1989). Along Florida's Gulf Coast, Milbrandt and Tinsley (2006) observed a greater number of black mangrove (Avicennia germinans (L.) Stearn) seedlings in existing B. maritima patches compared to surrounding mudfl ats. They hypothesized that this improved seedling success was the result of a slight increase in elevation provided by the B. maritima root system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another important ecological feature of B. maritima is its inability to tolerate prolonged periods of shade in mangrove-dominated wetlands (López-Portillo and Ezcurra, 1989). Along Florida's Gulf Coast, Milbrandt and Tinsley (2006) observed a greater number of black mangrove (Avicennia germinans (L.) Stearn) seedlings in existing B. maritima patches compared to surrounding mudfl ats. They hypothesized that this improved seedling success was the result of a slight increase in elevation provided by the B. maritima root system.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in salt marshes near its northern limit found that it was not a dominant species and did not compete well with other marsh plants (Zedler, 1977). There is some suggestion that B. maritima may be a fugitive species because it is common in disturbed sites (Milbrandt and Tinsley, 2006). Pennings and Richards (1998), for example, found that stands of B. maritima were associated with areas that were disturbed by wracks of litter in a Georgia salt marsh.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in other transitional systems, plant establishment and community succession is driven by tolerance to physiological stress and plant-plant interactions (Bertness, 1991;Milbrandt and Tinsley, 2006); hence species-specific competition could signify a natural blockage for landward migration of mangroves. However, in several cases, facilitation is a common mechanism of succession in terrestrial habitats, meaning that an early coloniser changes the abiotic conditions in a way that allows an entry and finally a displacement of a second species to a previous intolerable habitat ( Connell and Slayter, 1977).…”
Section: Vegetation Dynamics Of Mangrove Assemblages Under Different mentioning
confidence: 99%